Epidemiology of Hyperhidrosis in Danish Blood Donors - Mattias A.S. Henning; Kristina S. Ibler; Isabella Loft; Henrik Ullum; Christian Erikstrup; Kaspar R. Nielsen; Mie Topholm Bruun; Henrik Hjalgrim; Erik Sørensen; Kristoffer S. Burgdorf; Susan Mikkelsen; Thomas F. Hansen; et al. (Acta Dermato-Venereologica, 2021)

(untitled)
The risk factors and disease implications of hyperhidrosis are unknown. The objectives of this retrospective cohort study were to estimate the prevalence of hyperhidrosis and to compare demographic, lifestyle, and socioeconomic parameters in blood donors with and without self-reported or hospital-diagnosed hyperhidrosis. The study included blood donors from the Danish Blood Donor Study for the period 2010–2019. Registry data were collected from Statistics Denmark. Overall, 2,794 of 30,808 blood donors (9.07%; 95% confidence interval (95% CI) 8.75–9.40) had self- reported hyperhidrosis and 284 of 122,225 (0.23%; 95% CI 0.21–0.26) had hospital-diagnosed hyperhidrosis. Self-reported hyperhidrosis was associated with smoking (odds ratio (OR) 1.17; 95% CI 1.05–1.31), overweight (OR 1.72; 95% CI 1.58–1.87), “unemployed” (OR 1.60; 95% CI 1.24–2.08), “short education” (OR 0.76; 95% CI 0.64–0.90), and lower income (beta-coefficient –26,121; 95% CI –37,931, –14,311). Hospital-diagnosed hyperhidrosis did not differ from controls. Thus, self-reported hyperhidrosis was associated with potential hyperhidrosis risk factors (smoking, overweight) and disease implications (unemployment, low education level and income).